Magnetic Microdimer as Mobile Meter for Measuring Plasma Glucose and Lipids - Yu, Shimin; Sun, Zhongqi; Zhang, Zhanxiang; Sun, Haoran; Liu, Lina; Wang, Wuyi; Li, Mu; Zhao, Qingsong; Li, Tianlong (Frontiers in Bioengineering and Biotechnology, 2021)
With development of designed materials and structures, a wide array of micro/nanomachines with versatile functionalities are employed for specific sensing applications. Here, we demonstrated a magnetic propelled microdimer based point-of-care testing system can be used to provide the real-time data of plasma glucose and lipids relying on the motion feedback of mechanical properties. On-demand and programmable speed and direction of the microdimers can be achieved with the judicious adjustment of the external magnetic field, while their velocity and instantaneous postures provide estimation of glucose, cholesterol and triglycerides concentrations with high temporal accuracy. Numerical simulations reveal the relationship between motility performance and surrounding liquid properties. Such technology presents a point-of-care testing (POCT) approach to adapt to biofluid measurement, which advances the development of microrobotic system in biomedical fields.